Histone modification during the induction of tyrosine transaminase - Graaff, G De V (Department of Chemistry, 2020)
"The induction phenomenon is a useful model for the study of mechanisms which regulate the synthesis of specific enzymes in mammalian tissue, as well as for the role of hormones in this process". The in vivo administration of hormone initiates a chain of reactions which culminate in the increase of protein synthesis. Many hepatic enzymes are thus affected resulting in an increase of their activity. Studies of the giant chromosomes in the salivary glands of Chironomus tentans provided the first indications that the earliest intracellular effects of hormone administration are at the genetic level. Injection of the insect moulting hormone, ecdysone, into last instar larvae of Chironomus tentans results in puff formation at specific loci of the chromosomes shortly after hormone administration. Since puffs are local and reversible alterations of the chromosome, formed at sites which are active in the synthesis of informational RNA, their formation shows a change in activity of particular gene loci in response to ecdysone.